Single Mothers, Low Income and Women's Economic Risks. The Cases of Sweden, West Germany and the United States - Annemette Sorensen (Luxembourg Income Study (LIS), 1990)
The economic position of single mother households in West Germany, Sweden, and the U.S. is examined.
Keywords: 330